VISUALISASI SEBAGAI UPAYA UNTUK MEMAHAMI MATERI TEORITIS DI DALAM PERKULIAHAN - Riesta Harsalinda; Primardiana Hermilia Wijayati (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2018)
This study attempts to described understanding students in learning lecture evaluation of teaching language germany with using a technique visualize. Methods used in research is descriptive quantitative method. An instrument used the video visualize, material exercise, questionnaires and documents. Material test competence language productive, receptive and literature presented in the form of video .The contents of material displayed with a variation of color, size of letters, a picture, illustrations and audio. The result of research is third of the material well understood by students because display visualizations served interesting and clear, The preparation of a groove material well furnished by example and training make the material into more easily understood.